2012
DOI: 10.1037/a0025841
|View full text |Cite
|
Sign up to set email alerts
|

Conditional reasoning difficulties in polysubstance-dependent patients.

Abstract: Polysubstance dependence has been associated with many neurocognitive impairments. The present study explored one of these deficits, namely conditional reasoning, using the Wason selection task. In healthy individuals, social contract and precautionary content improve conditional reasoning performance compared with descriptive or abstract content. Twenty-two recently detoxified polysubstance-dependent patients were compared with 22 controls matched for sex, age, and education level on their performance on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On a cognitive level, addiction is generally considered as an imbalance between two systems, which are both (indirectly) mediated by dopaminergic systems and smoking addiction does not break the rule (Bassareo and Di Chiara, 1999; Pontieri et al, 1995; Stacy and Wiers, 2010; Tanda et al, 1997). Several models refer to this dual-process theory as a global explanation for addiction including its development, maintenance, and relapse (Goldstein and Volkow, 2002; Kornreich, et al, 2012; Kreusch et al, 2013; Noël et al, 2010; Robinson and Berridge, 1993; Wiers et al, 2007). Indeed, among the strongest clinical evidence for addiction is both the reactivity towards addiction-related stimuli at the one hand, and the inability to refrain from their approach at the other.…”
Section: Introductionmentioning
confidence: 99%
“…On a cognitive level, addiction is generally considered as an imbalance between two systems, which are both (indirectly) mediated by dopaminergic systems and smoking addiction does not break the rule (Bassareo and Di Chiara, 1999; Pontieri et al, 1995; Stacy and Wiers, 2010; Tanda et al, 1997). Several models refer to this dual-process theory as a global explanation for addiction including its development, maintenance, and relapse (Goldstein and Volkow, 2002; Kornreich, et al, 2012; Kreusch et al, 2013; Noël et al, 2010; Robinson and Berridge, 1993; Wiers et al, 2007). Indeed, among the strongest clinical evidence for addiction is both the reactivity towards addiction-related stimuli at the one hand, and the inability to refrain from their approach at the other.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of psychopathic subjects ( Ermer & Kiehl, 2010 ), verbal IQ, measured with the Wechsler Adult Intelligence Scale (WAIS), was not responsible for the differences observed in conditional reasoning for social contract or precautionary reasoning, whereas in the present study, verbal IQ was correlated with appropriate social contract reasoning but not reasoning about precautions or descriptive rules. The same assessment of vocabulary scales (Mill Hill) was used in a study on conditional reasoning in alcoholics ( Kornreich et al, 2011 ) and in polydrug abusers ( Kornreich et al, 2012 ) and was not responsible for the differences observed in the Wason test between patients and controls. As verbal IQ reflects not only vocabulary extent but also attentional and memory functioning, further neuropsychological assessments, that is, memory, attention, and more generally executive functions, should be used in future studies to disentangle what kind of precise neuropsychological impairment is responsible here for conditional reasoning scores differences between patients with schizophrenia patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment was present on social contract, precautionary, and descriptive reasoning in alcoholics, but was especially severe with descriptive rules, where alcoholic patients’ performance was at chance. In polysubstance dependence patients ( Kornreich et al, 2012 ), social contract and descriptive reasoning was not above chance level, while precautionary reasoning was relatively preserved—worse than in controls but largely above chance level. All these results could reflect dysfunctions in prefrontal functioning.…”
mentioning
confidence: 82%